The effects of policy changes in labor mobility and its impact on competitiveness among firms: evidence from the football industry´s bosman ruling - Boström, Nils August Ask (2021)
In an ever so increasing globalized world where businesses and societies move towards a knowledge-based economy, firms must maintain their competitiveness through acquisition and the retention of high-skilled workers. Based on economists’ theories of tacit knowledge and adverse selection among employees, disruption of the policies in place of international labor mobility might alter the competitive landscape among firms in an industry. Using the industry of football in Europe, imbued with tacit knowledge, this thesis setsout to analyze how policy changes in labor mobility affects firm competitiveness. With the emergence of the European single market, high-skilled workers within the EU are able to relocate with ease and employers are able to draw from a significantly larger pool of potential employees. Comparatively, the policy change of the Bosman ruling liberalized the labor market for football players and shares resemblance with a free-trade environment as opposed to a restrictive market prior to the ruling. On the basis of economic theory on sources of competitiveness and labor mobility, this thesis empirically investigates the evolution of the competitiveness in the football industry and how the Bosman ruling affected it. Secondary data was used to capture various measurements of performance, such as football club performance, national team performance, club expenditure and labor mobility of football players. Results show that firm competitiveness is significantly affected by imposing policy changes in labor mobility, greatly benefiting clubs in the five largest European football countries. The thesis also hints to a large underlying reason of competitive imbalances in the industry, which are financial resources. Moreover, arguments of restrictive labor mobility are brought up and analyzed from a domestic economies perspective and are found to be valid in the extent of this thesis.